Human Connections and Their Roles in the Occupational Well-being of Healthcare Professionals: A Study on Loneliness and Empathy - Soler-Gonzalez, Jorge; San-Martín, Montserrat; Delgado-Bolton, Roberto; Vivanco, Luis (Frontiers in Psychology, 2017)
Human connections are key to the promotion of health and prevention of illness; moreover, illness can cause deterioration of human connections. Healthcare professional-patient relationships are key to ensuring the preservation of adequate human connections. It is important for healthcare professionals to develop their ability to foster satisfactory human connections because: (i) they represent social support for patients; and (ii) they prevent work-related stress. In this study we assessed the relationship between absence (loneliness) and presence (empathy) of human connections with the occupational well-being of healthcare professionals. The Scale of Collateral Effects, which measures somatization, exhaustion, and work alienation; the Jefferson Scale of Empathy; and the Social and Emotional Loneliness Scale for Adults, were mailed to 628 healthcare professionals working in Spanish public healthcare institutions. The following explanatory variables were used to evaluate work well-being: (a) empathy, as a professional competence; (b) loneliness, age, and family burden, as psychological indicators; and (c) professional experience, work dedication, and salary, as work indicators. Comparison, correlation, and regression analyses were performed to measure the relationships among these variables and occupational well-being. Of 628 surveys mailed, 433 (69% response rate) were returned fully completed. Adequate reliability was confirmed for all instruments. The entire sample was divided into four groups, based on the combined variable, “occupation by sex”. Comparative analyses demonstrated differences among “occupation by sex” groups in collateral effects (p = 0.03) and empathy (p = 0.04), but not loneliness (p = 0.84). Inverse associations between empathy and collateral effects were confirmed for somatization (r = –0.16; p < 0.001), exhaustion (r = –0.14; p = 0.003), and work alienation (r = –0.16; p < 0.001). Furthermore, loneliness was positively associated with collateral effects (r = 0.22; p < 0.001). Neither family burden, nor work dedication to clinics or management activities were associated with the three collateral effects measured. These findings support an important role for empathy in the prevention of work stress in healthcare professionals. They also confirm that loneliness, as a multidimensional and domain specific experience, is detrimental to occupational well-being.